Growth performance and nutritive quality of tree Lucerne (Chamaecytisus palmensis) fodder under different management conditions in the Highlands of Ethiopia - Tadesse, F. (Hawassa University, 2016)
Tagasaste (Chamaecytisus palmensis), also known as tree Lucerne, is an evergreen, hardy leguminous shrub that is adapted to high lands of Ethiopia. The objective of this study was to evaluate growth performance of tree lucerne in terms of survival, root collar diameter (RCD), plant height and biomass yield as influenced by different management. To conduct the present study three highlands districts (woredas) located in southern region (Lemo), in Oromia region (Sinana) and Tigrai region (Endamehoni) were selected. Within each woreda, two kebeles were purposely selected to be used as action sites, and from each kebele a minimum of 25 farmers were selected to participate in tree Lucerne adaptation trials. Each farmer received about 150 seedlings to plant and grow. Data were collected on feed resources, household characteristics and survival and performance of the seedlings. The tree lucerne fodder plots established and performed well were used to collect data on the effect of cutting height, and cutting frequency on the biomass yield of fodder. The fodder plants were subjected to two cutting heights (1m and 1.5m), and three cutting frequencies (2, 3, 4 times per year). The average household family size and livestock holdings were 8.08 heads and 10.35 heads, respectively. According to the result about 66% of the land was used for crop cultivation and the remaining 34% was apportioned into improved forage and other back yard trees in the study area. About 85.4% respondents perceived that the landholding size is decreasing, while about 13% of the farmers said that it remained stable over the years. Grazing (both private and communal) contributed the largest share of the feed resources, followed by crop residues. About 44% of the farmers mentioned that their main reason for engaging in tree lucerne cultivation is to produce livestock feed supplement. The maximum survival rate was observed for plants which grew around backyard on small plot followed by that grown on the contour lines, whereas the lowest survival rate was achieved from plants grown around water logged areas. Transplanting too small seedlings showed lower (p<0.05) survival rate as compared to the remaining agronomic and management practices. Planting space of 100cm between rows and 100cm between plants resulted in significantly (p<0.05) higher dry matter yield than 50x50cm spacing. Tree lucerne showed accelerated growth in terms of height and RCD after six months. Annual biomass production was substantially greater for six months cutting interval than for the more frequent harvests in a range of 4.17 to 8.22 t ha–1. Whereas, the two cutting height not showed significant (p<0.05) differences on biomass yield. Leaf proportion of the biomass yield consistently decreased from 63.55 to 54.52% and the stem increased from 2.38 to 16.54% as the cutting interval prolonged from three to six months, respectively. The crude protein contents for the month of June (28%) was significantly (p<0.05) higher than that of October (24.6%), whereas, the other months had intermediate value. There were no significant (p<0.05) differences in IVOMD and ME contents among the different cutting months. The current study revealed that with proper management practices, tree Lucerne can be a suitable protein supplement for ruminant livestock in the study areas.